2005
DOI: 10.1111/j.1475-097x.2004.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of non‐invasive endothelial function assessment by brachial artery flow‐mediated dilatation

Abstract: A non-invasive technique using high-frequency ultrasound brachial artery imaging to assess endothelium-dependent flow-mediated vasodilatation is a widely used test, but interpretation of results is not consistent. This study was designed to assess the method of non-invasive endothelial function determination of a brachial artery. Endothelial function was assessed by two physicians in 18 young, healthy volunteers. Each volunteer was examined by both physicians on the same day using an identical protocol; a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…Therefore, depending on the BBAD, higher BAFMD values can be found, which does not necessarily reflect better artery function. In the present study, no significant correlations were found between BBAD and BAFMD, which agrees with the observations of Šejda et al 25 but disagrees with the results of Herrington et al 8 .…”
Section: Same Day Separate Dayssupporting
confidence: 53%
“…Therefore, depending on the BBAD, higher BAFMD values can be found, which does not necessarily reflect better artery function. In the present study, no significant correlations were found between BBAD and BAFMD, which agrees with the observations of Šejda et al 25 but disagrees with the results of Herrington et al 8 .…”
Section: Same Day Separate Dayssupporting
confidence: 53%
“…38,39 The variability of measurements carried out at intervals by the same operator is satisfactory, whereas the inter-observer variability is exceedingly high. 40 Accordingly, in the current study all tests were performed by the same operators in two different units, after careful training. Measured mean values were on average slightly higher than previously reported in several methodological studies, 40,41 but the young age of our population and the low prevalence of complicating diseases are a likely explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is considered the current 'gold standard,' assessment of flow mediated dilatation poses several important challenges. In order to have adequate within laboratory reproducibility, administering this test requires very specialised training for the ultrasound technician, and even with extensive training, there is generally poor between laboratory reliability [33]. These limitations have meant that flow mediated dilatation has had limited clinical utility [34].…”
Section: Introductionmentioning
confidence: 99%